Odpowiedzi

2010-01-07T22:00:08+01:00
A) 6y-2x=9
3y=x-6 / - x

6y-2x=9
3y - x = - 6 / * (-2)

6y-2x=9
- 6y + 2x = 12

0= 21

Równanie jest sprzeczne. Czyli nie ma rozwiązania.

b) 2y=x
x-jedna druga=0

2y - 1/2 = 0 / + 1/2
2y = 1/2 / *2
4y = 1 / : 4
y = 1/4

x=1/2
y= 1/4


c) 2x+x=3 / - 2x
y-1,5=-0,5x

y-1,5=-0,5x
3x = 3 / :3

y-1,5=-0,5x
x= 1

y - 1,5 = - 0,5 / +1,5
y = 1

y= 1
x = 1


1 5 1
2010-01-07T22:06:45+01:00
A)
6y-2x=9
3y=x-6

3y=x-6
6y-2x=9

3y + 6 = x
6y -2(3y+6) = 9

x = 3y +6
6y - 6y -12 = 9

x = 3y + 6
0 = 9 +12 sprzeczne - brak rozwiązania


b)
2y=x
x-jedna druga=0

x = 2y
x - 1/2 = 0

x = 2y
x = 1/2

2y = 1/2 /:2
x = 1/2

x = 1/2
y = 1/4

c)
2x+x=3
y-1,5=-0,5x wszystko w klamrach

3x = 3
y + 0,5x = 1,5

x = 1
y + 0,5*1 = 1,5

x = 1
y = 1,5 - 0,5 = 1

x = 1
y = 1

1 5 1